Corga Magazine (2010-2016): Analysis, Trajectory and Influence of a Magazine to Promote the Galician Language and the Tangible and Intangible Heritage of O Corgo - Doucet, Montserrat (Madrygal. Revista de Estudios Gallegos, 2020)
In March 2009, Corgo Studies Center is constituted within the Galician rural environment as a non-profit association among other objectives proposed defense of the culture and the language of Galicia as well as different multidisciplinary studies of the natural heritage, material and immaterial of the concello de O Corgo. The annual magazine Corga is one of the instruments that makes it possible to achieve these objectives. We will try to analyze throughout their six numbers as it reflected the cultural part of the Galician people concerns and as influenced in their environment.
Keywords: Galician Rural; Arumes Association; O Corgo; Tangible Heritage; Intangible Heritage